Critical Factors in Police Use-of-Force Decisions - Nickel, Orville (2015)
This study investigated law enforcement officers' perceptions of the legal, normative, and practical considerations that are implicit in their decisions when faced with using physical force. Law enforcement officers observe and protect fundamental human rights. A significant problem, however, is that physical force is sometimes misused, impacting public confidence in police services. The study was framed by Durkheim's conflict theory and Beirie's concepts of police corporate culture and social control. It used a grounded theory method and predeveloped case scenarios presented to 2 male focus groups of 7 and 6 participants respectively, and 2 female focus groups of 5 and 7 participants, who were police officers in Canada, to explore for gender differences in response strategies, decisions to use force, and arguments for their decisions, following the model set forth by Waddington (2009). Additionally, data were also collected through 12 individual semistructured interviews. Open, axial, and selective manual coding was used in the data analysis. The data collection and analysis for this study resulted in the development of, the paradigm of safety, a theory that reflects how female officers' use-of-force decisions differ from the decisions of their male colleagues. These decision factors, when incorporated into their response strategies, reflect the timing and need for using force. This study promotes positive social change by providing information that will inform police policies and training practices. This information will enable police administrators and legislators to enhance workplace safety for their officers that are more consistent with democratic rights and freedoms for citizens by reducing use-of-force in conflict circumstances